Design of Mosque Ablution Areas for Disabled: Evaluation of Ministerial Regulation of Public Works and Public Housing No. 14/2017 - Rinaldy Yumadhika; Arif Budi Sholihah (Departement of Architecture, Universitas Islam Indonesia, 2019)
Equality for disabled is regulated in Indonesia including the right to embrace religion, to access, and to use worship facilities. Disabled in Indonesia still becomes a minority group even though the number of disabled is considerably large. The Province of Special Region of Yogyakarta is ranked second as the highest number of disabled, the high number of people with disabilities should be directly proportional to the providing of disability-friendly worship facilities. Ablution area is one of the facilities that the presence is very much needed to cleanse ourselves before performing worship. This study aims to determine the elements that affect the accessibility of the ablution area for the disabled and to recommend a design that has been considered with the ability of the disabled. This study uses a qualitative method with a naturalistic approach, which is following the existing conditions toward a case study of the Great Mosque of Manunggal Bantul. Data collection is conducted by simulating the access to ablution area by the disabled and expert interviews, which are architects to help researchers produce a design that is disabled-friendly, the validity of the data is done by triangulation between the simulation results and the results of expert interviews compared to the Ministerial Regulation of Public Works and Public Housing No. 14/2017. Simulation results that are followed by expert interviews show several elements that affect the accessibility of the ablution area: ramp, steering tile, handrail, information on space, stair, chair for ablution, faucet, grill, floor material, and place of good. Comparative results of the regulations show that some elements that have not explained yet about the ablution area that is disabled-friendly, the regulation only describes the ablution area for the disabled by sitting with and without wheelchair equipped with handrails. Recommended designs are ramp, directional tile, handrail, room information, stair, chair for ablution, faucet, grill, floor surface, and items that have been considered with disability.Keywords: accessibility, differential disabled, ablution area, ablution, ministerial regulation